2015
DOI: 10.1007/s11356-015-5607-z
|View full text |Cite
|
Sign up to set email alerts
|

Application of veterinary antibiotics in China’s aquaculture industry and their potential human health risks

Abstract: China contributes to more than 60 % of the global aquaculture production, and its aquaculture industry has become one of the main players in food security. A large amount of antibiotics is believed to be used in fish cultivation for ensuring adequate production. The use of antibiotics as disease control agents and growth promoter in aquaculture in China has raised significant concerns recently because of the potential threats to human health. The extensive use of antibiotics in aquaculture may result in water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
93
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(100 citation statements)
references
References 93 publications
2
93
0
5
Order By: Relevance
“…Similar research was observed in Japan (Wimalasena et al, ), while the previous study showed E. tarda was sensitive to streptomycin and florfenicol (Fukui, Fujihara, & Kano, ; Muyembe et al, ). Florfenicol can be administered via feed to aquatic animals, which could significantly enhance growth performance and control the mortality due to bacterial infection (Mo, Chen, Leung, & Leung, ). However, the application of antibiotic in feed might lead to the emergence of antibiotic‐resistant isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Similar research was observed in Japan (Wimalasena et al, ), while the previous study showed E. tarda was sensitive to streptomycin and florfenicol (Fukui, Fujihara, & Kano, ; Muyembe et al, ). Florfenicol can be administered via feed to aquatic animals, which could significantly enhance growth performance and control the mortality due to bacterial infection (Mo, Chen, Leung, & Leung, ). However, the application of antibiotic in feed might lead to the emergence of antibiotic‐resistant isolates.…”
Section: Discussionmentioning
confidence: 99%
“…2015; Sahoo, Jena, Patel, & Seshadri, 2016). To maintain sustainable aquaculture production, in last few decades, antibiotics and chemotherapeutics as traditional drugs were commonly used for infectious diseases treatment and prevention, accompanying by a risk of emergence of microbial dysbiosis, resistant pathogenic bacteria, and accumulation of antibiotics in aquaculture food products which led to food safety issues for human health (Liu, Steele, & Meng, 2017;Mo, Chen, Leung, & Leung, 2017). Therefore, the development of natural and eco-friendly methods such as non-antibiotic farming is widely accepted in Chinese aquaculture industry and globally as well (Schmidt, Gomezchiarri, Roy, Smith, & Amaralzettler, 2017).…”
mentioning
confidence: 99%
“…The rapid development of aquaculture not only provides a lot of food but also creates extremely high economic benefits for human beings (Wang et al, ). As one of the primary industries in China, aquaculture accounts for approximately 71% of the global aquaculture production (Mo, Chen, Leung, & Leung, ). Liaodong Bay is a part of Bohai and the inlet of the Liaohe and Daling River in northeast China.…”
Section: The Water Parameters Of Samplesmentioning
confidence: 99%